Post Traumatic Stress Disorder in Jordan Peele's US - Athaya Almira Nur Azzahra (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2022)
At some point in their lives, most people will experience traumatic events. Traumatic stress can trigger a variety of response patterns, ranging from a temporary disruption of functioning to chronic conditions such as Post Traumatic Stress Disorder (PTSD). A variety of methods and criteria are used in epidemiologic studies to assess trauma and PTSD, which vary in prevalen. Throughout this study, qualitative descriptive methods are used. The writer uses the trauma approach of Sigmund Freud and the theory of Post-Traumatic Stress Disorder or PTSD to describe the symptoms experienced by Adelaide and also analyses how the survivors' families respond, especially when helping survivors calm themselves. This study aims to depict PTSD symptoms in US and reveal the effects of PTSD on the family survivor. By using the trauma theory approach by Sigmund Freud, the writer concludes that someone who experienced traumatic events as a child can affect their adulthood. The symptoms experienced also affect the people closest to them. As a result of this trauma, Adelaide still feels haunted by dark shadows from her past and panics when triggered by places where she experienced terrible incidents.